2022
DOI: 10.31234/osf.io/cs8zv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Specific types of childhood abuse and neglect and profiles of adult emotion dynamics

Abstract: Childhood maltreatment (CM) is experienced by ~40% of all children at major personal and societal costs. Studies show adverse consequences of CM on emotional functioning and regulation. This article focuses on differential imprint of emotional, physical, and sexual abuse and/or neglect exteriences during childhood on emotional functionin later in life To study this, we calculated how intense, variable, unstable, inert, and diverse the daily emotions were of 290 Dutch adults (aged 19-73, measured thrice daily d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 98 publications
0
1
0
1
Order By: Relevance
“…Previously, we argued that once children become adults, and feel that they no longer can be physically hurt, they may feel that their future is unlikely to be as bad as their past has been (a sense of control), which may result in fast recovery (resilience) or even show some positive growth. Some previous research is in line with this idea, as physical abuse has been found to be associated with an array of positive adult outcomes, such as higher positive affect, lower depressive and anxiety symptoms, more happiness, self-acceptance, personal autonomy, higher control and coping, among others (Jeronimus et al, 2023;Sudbrack et al, 2015).…”
Section: Physical Abusementioning
confidence: 63%
“…Previously, we argued that once children become adults, and feel that they no longer can be physically hurt, they may feel that their future is unlikely to be as bad as their past has been (a sense of control), which may result in fast recovery (resilience) or even show some positive growth. Some previous research is in line with this idea, as physical abuse has been found to be associated with an array of positive adult outcomes, such as higher positive affect, lower depressive and anxiety symptoms, more happiness, self-acceptance, personal autonomy, higher control and coping, among others (Jeronimus et al, 2023;Sudbrack et al, 2015).…”
Section: Physical Abusementioning
confidence: 63%
“…Met de daar aanwezige expertise kun nen we longitudinale vragenlijststudies aanvullen met obser vaties om zo dicht mogelijk bij die daadwerkelijke situatie te komen. Ik zie verschillende mogelijkheden om hierin samen te werken met Marijn van Dijk, Laura Cuijpers, maar ook Peter de Jonge, Annelieke Roest, Solemiia Myroniuk (die eerder al de variabiliteit in emoties onderzocht als reactie op het meemaken van verschillende vormen van geweld en verwaarlozing in de kindertijd [26]) en Bertus Jeronimus (die een scoping review uitvoerde naar Nederlandse systeemgerichte interventies bij slachtofferschap van huiselijk geweld [11]).…”
Section: Intergenerationeleunclassified